Survival of the Fittest (?) : The Endurance of the ROC Constitution and t he Constitution of Japan. (1st July 2014) - Lin, Chien-Chih
Abstract: Conventional wisdom has it that the endurance of a constitution hinges on the interaction of design factors and environmental elements. For a constitution to be long-lasting, it needs to be not only self-enforcing domestically, but also resilient when facing international cataclysm. Yet these macro theories fail to tackle the nuanced variances in each constitution, especially those in East Asian countries. Attempting to fill this academic lacuna, this Article compares the Constitution of the Republic of China and the Constitution of Japan, two stable constitutions that have not been replaced since World War II. It suggests that although there are some similarities, factors that contribute to the longevity of the two constitutions are quite different. The durability of the Constitution of Japan could be better explained through the lens of constitutional design. By contrast, the stability of the ROC Constitution results mainly from environmental reasons irrelevant to the parchment barrier itself.